Melanogenesis‐Inhibitory Activity and Cancer Chemopreventive Effect of Glucosylcucurbic Acid from Shea (Vitellaria paradoxa) Kernels. Issue 4 (April 2015) - Zhang, Jie; Kurita, Masahiro; Ebina, Kodai; Ukiya, Motohiko; Tokuda, Harukuni; Yasukawa, Ken; Masters, Eliot T.; Shimizu, Naoto; Akihisa, Momoko; Feng, Feng; Akihisa, Toshihiro
Abstract Two jasmonate derivatives, glucosylcucurbic acid (1) and methyl glucosylcucurbate (2), were isolated from the MeOH extract of defatted shea (Vitellaria paradoxa; Sapotaceae) kernels. These and their deglucosylated derivatives, cucurbic acid (3) and methyl cucurbate (4), were evaluated for their melanogenesis‐inhibitory and cancer chemopreventive potencies. Compounds 1, 3, and 4 exhibited potent melanogenesis‐inhibitory activities in α‐melanocyte‐stimulating hormone (α‐MSH)‐stimulated B16 melanoma cells. Western‐blot analysis revealed that compounds 1 and 3 reduced the protein levels of MITF (=microphthalmia‐associated transcription factor), tyrosinase, TRP‐1 (=tyrosine‐related protein 1), and TRP‐2 mostly in a concentration‐dependent manner. In addition, compound 1 exhibited inhibitory effects against EpsteinBarr virus early antigen (EBV‐EA) activation induced with 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA) in Raji cells, against TPA‐induced inflammation in mice, and against skin tumor promotion in an in vivo two‐stage mouse skin carcinogenesis test based on 7, 12‐dimethylbenz[a]anthracene (DMBA) as initiator, and with TPA as promoter.